PENGARUH PELATIHAN, KECANGGIHAN TEKNOLOGI, PENGALAMAN KERJA, DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA KOPERASI SIMPAN PINJAM DI KECAMATAN ABIANSEMAL - Ni Putu Lisa Ernawatiningsih; I Ketut Sunarwijaya (Jurnal Bakti Saraswati (JBS), 2024)
The effectiveness of using accounting information systems is the quality and quantity of a collection of resources, both human and equipment, that are arranged to convert accounting data into accounting information for decision making. This research aims to examine the influence of user participation, training, education level, work experience, and top management support on the performance of accounting information systems in savings and loan cooperatives in Abiansemal District. The population of this study was 30 savings and loan cooperatives located in Abiansemal District. The sample in this study was 36 employees of the Abiansemal District savings and credit cooperative who were directly involved in the use of the accounting information system which was determined based on the purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression analysis. The research results show that work experience have a positive effect on the effectiveness of using accounting information systems. Meanwhile, the training, sophistication of information technology and top management support have no effect on the effectiveness of using accounting information systems